Skip to content
🎉 DeepSeek-R1 🥳
question:Compute 47^{2045} - 18^{2045} modulo 6.

answer:First, I need to simplify the expression (47^{2045} - 18^{2045}) modulo 6. I'll start by finding the equivalents of 47 and 18 modulo 6.Calculating (47 mod 6), I find that (47 equiv 5 mod 6), which is the same as (47 equiv -1 mod 6). For (18 mod 6), it's straightforward that (18 equiv 0 mod 6).Next, I'll raise these equivalents to the power of 2045. Since (47 equiv -1 mod 6), raising it to any power will depend on whether the exponent is odd or even. In this case, 2045 is odd, so ((-1)^{2045} = -1). For (18), since it's equivalent to 0 modulo 6, any power of 0 remains 0.Finally, I'll subtract the two results: (-1 - 0 = -1). To express this as a positive residue modulo 6, I add 6 to (-1), resulting in 5. Therefore, (47^{2045} - 18^{2045} equiv 5 mod 6).

question:How many positive integers, including 1, are divisors of both 36 and 54?

answer:To determine how many positive integers, including 1, are divisors of both 36 and 54, I will follow these steps:1. **Prime Factorization**: - **36**: Break down 36 into its prime factors. 36 can be expressed as (2^2 times 3^2). - **54**: Similarly, break down 54 into its prime factors. 54 can be expressed as (2^1 times 3^3).2. **Identify Common Prime Factors**: - Both numbers share the prime factors 2 and 3.3. **Determine the Minimum Powers**: - For the prime factor 2, the minimum power between 36 ((2^2)) and 54 ((2^1)) is (2^1). - For the prime factor 3, the minimum power between 36 ((3^2)) and 54 ((3^3)) is (3^2).4. **Calculate the Greatest Common Divisor (GCD)**: - Multiply the minimum powers of the common prime factors: (2^1 times 3^2 = 2 times 9 = 18).5. **Find Divisors of the GCD**: - The divisors of 18 are 1, 2, 3, 6, 9, and 18.6. **Count the Divisors**: - There are 6 positive integers that are divisors of both 36 and 54.

question:The necessary and sufficient condition for the inequality x^{2}-2x+m > 0 to hold true in R is ( )A: m > 2B: 0 < m < 1C: m > 0D: m > 1

answer:Okay, so I have this inequality: (x^2 - 2x + m > 0). The question is asking for the necessary and sufficient condition for this inequality to hold true for all real numbers (x). The options are A: (m > 2), B: (0 < m < 1), C: (m > 0), and D: (m > 1).Hmm, I remember that for a quadratic equation (ax^2 + bx + c), the graph is a parabola. Since the coefficient of (x^2) here is 1, which is positive, the parabola opens upwards. That means the minimum value of the quadratic is at its vertex. So, if the quadratic is always positive, the vertex must be above the x-axis.To find the vertex, I can use the formula for the vertex of a parabola. The x-coordinate of the vertex is at (-b/(2a)). In this case, (a = 1) and (b = -2), so the x-coordinate is (-(-2)/(2*1) = 2/2 = 1). Now, to find the y-coordinate of the vertex, I plug (x = 1) back into the equation: (1^2 - 2*1 + m = 1 - 2 + m = -1 + m). So, the vertex is at ((1, m - 1)).For the quadratic to be always positive, the y-coordinate of the vertex must be greater than zero. That means (m - 1 > 0), which simplifies to (m > 1). So, (m) must be greater than 1.Wait, let me double-check that. Another way to ensure the quadratic is always positive is to check the discriminant. The discriminant of a quadratic equation (ax^2 + bx + c) is (b^2 - 4ac). If the discriminant is negative, the quadratic doesn't cross the x-axis and is always positive (since (a > 0)).Calculating the discriminant for (x^2 - 2x + m), we have (b^2 - 4ac = (-2)^2 - 4*1*m = 4 - 4m). For the quadratic to be always positive, we need (4 - 4m < 0). Solving this inequality:(4 - 4m < 0)Subtract 4 from both sides:(-4m < -4)Divide both sides by -4, remembering to reverse the inequality sign when dividing by a negative number:(m > 1)Okay, so that confirms it. The discriminant method also gives (m > 1). So, the necessary and sufficient condition is (m > 1), which is option D.Wait, but the initial thought process I had earlier led me to think that the answer was C: (m > 0). But that seems conflicting. Let me figure out where I went wrong.Looking back, I considered the vertex at (x = 1), and the y-coordinate was (m - 1). So, for the quadratic to be positive everywhere, (m - 1 > 0) is necessary. That gives (m > 1). So, why did I think the answer was C earlier? Maybe I confused it with another problem.Alternatively, perhaps I considered the quadratic (x^2 + m), which would have a discriminant of (0 - 4*1*m = -4m), requiring (m > 0). But in this problem, the quadratic is (x^2 - 2x + m), so the discriminant is different.Therefore, the correct condition is (m > 1), which is option D.Wait, but let me think again. If (m > 1), then the quadratic is always positive. If (m = 1), the quadratic becomes (x^2 - 2x + 1 = (x - 1)^2), which is zero at (x = 1), so it's not strictly positive everywhere. If (m < 1), then the quadratic will have real roots and will dip below the x-axis between them, so it won't be positive everywhere.Therefore, the necessary and sufficient condition is indeed (m > 1), which is option D.But wait, looking back at the initial problem, the options are A: (m > 2), B: (0 < m < 1), C: (m > 0), D: (m > 1). So, D is the correct answer.I think initially I might have made a mistake in recalling the problem or miscalculating, but after carefully going through both the vertex method and the discriminant method, it's clear that (m > 1) is the correct condition.So, the answer should be D: (m > 1).

question:Evaluate the expression sqrt{frac{9}{2}} + sqrt{frac{2}{9}}.textbf{(A)} frac{5sqrt{2}}{6}qquadtextbf{(B)} frac{10sqrt{2}}{6}qquadtextbf{(C)} frac{11sqrt{2}}{6}qquadtextbf{(D)} frac{7sqrt{2}}{6}qquadtextbf{(E)} frac{8sqrt{2}}{6}

answer:First, I need to simplify each square root separately. Starting with √(9/2), I can separate the square root of the numerator and the denominator, which gives me √9 divided by √2. Since √9 is 3, this simplifies to 3/√2. To rationalize the denominator, I multiply both the numerator and the denominator by √2, resulting in (3√2)/2.Next, I simplify √(2/9). Similarly, I separate the square root of the numerator and the denominator, which gives me √2 divided by √9. Since √9 is 3, this simplifies to √2/3.Now, I need to add the two simplified expressions: (3√2)/2 and √2/3. To add these fractions, I must find a common denominator. The least common denominator of 2 and 3 is 6. I convert each fraction to have this common denominator: (3√2)/2 becomes (9√2)/6, and √2/3 becomes (2√2)/6.Finally, I add the two fractions: (9√2)/6 + (2√2)/6 equals (11√2)/6. This is the simplified form of the original expression.

question:Evaluate the definite integral ∫_{-2}^{2}|x^{2}-2x|dx=A: 5B: 6C: 7D: 8

answer:Alright, so I've got this integral to solve: the definite integral from -2 to 2 of the absolute value of (x squared minus 2x) dx. Hmm, okay. I remember that when dealing with absolute values inside integrals, I need to figure out where the expression inside the absolute value changes sign because that will determine how I split the integral.First, let me write down the integral:∫_{-2}^{2} |x² - 2x| dxI need to find where x² - 2x equals zero because that's where the expression inside the absolute value will change its sign. So, let's solve x² - 2x = 0.x² - 2x = 0x(x - 2) = 0So, the solutions are x = 0 and x = 2. That means the expression x² - 2x is zero at x = 0 and x = 2. Now, I need to test the intervals between these points to see where the expression is positive or negative.The intervals are:1. From -2 to 02. From 0 to 2Let me pick a test point in each interval.First interval: Let's choose x = -1.Plugging into x² - 2x:(-1)² - 2*(-1) = 1 + 2 = 3, which is positive.Second interval: Let's choose x = 1.Plugging into x² - 2x:(1)² - 2*(1) = 1 - 2 = -1, which is negative.So, the expression x² - 2x is positive from -2 to 0 and negative from 0 to 2. Therefore, the absolute value will affect the sign in each interval accordingly.That means I can split the integral into two parts:∫_{-2}^{0} (x² - 2x) dx + ∫_{0}^{2} -(x² - 2x) dxSimplifying the second integral:∫_{-2}^{0} (x² - 2x) dx + ∫_{0}^{2} (-x² + 2x) dxNow, I can compute each integral separately.Let's start with the first integral: ∫_{-2}^{0} (x² - 2x) dxThe antiderivative of x² is (1/3)x³, and the antiderivative of -2x is -x². So, putting it together:[ (1/3)x³ - x² ] from -2 to 0Let's evaluate at the upper limit (0):(1/3)(0)³ - (0)² = 0 - 0 = 0Now, evaluate at the lower limit (-2):(1/3)(-2)³ - (-2)² = (1/3)(-8) - 4 = (-8/3) - 4Convert 4 to thirds to combine: 4 = 12/3So, (-8/3) - (12/3) = (-20/3)Now, subtract the lower limit from the upper limit:0 - (-20/3) = 20/3Okay, so the first integral evaluates to 20/3.Now, moving on to the second integral: ∫_{0}^{2} (-x² + 2x) dxFirst, let's find the antiderivative. The antiderivative of -x² is (-1/3)x³, and the antiderivative of 2x is x². So, putting it together:[ (-1/3)x³ + x² ] from 0 to 2Evaluate at the upper limit (2):(-1/3)(2)³ + (2)² = (-1/3)(8) + 4 = (-8/3) + 4Convert 4 to thirds: 4 = 12/3So, (-8/3) + (12/3) = 4/3Now, evaluate at the lower limit (0):(-1/3)(0)³ + (0)² = 0 + 0 = 0Subtract the lower limit from the upper limit:4/3 - 0 = 4/3So, the second integral evaluates to 4/3.Now, add the two results together:20/3 + 4/3 = 24/3 = 8Wait, that seems straightforward, but let me double-check my calculations to make sure I didn't make any mistakes.First integral:[ (1/3)x³ - x² ] from -2 to 0At 0: 0 - 0 = 0At -2: (1/3)(-8) - 4 = (-8/3) - 4 = (-8/3) - (12/3) = (-20/3)Difference: 0 - (-20/3) = 20/3. That seems correct.Second integral:[ (-1/3)x³ + x² ] from 0 to 2At 2: (-8/3) + 4 = (-8/3) + (12/3) = 4/3At 0: 0 + 0 = 0Difference: 4/3 - 0 = 4/3. That also seems correct.Adding them together: 20/3 + 4/3 = 24/3 = 8. So, the total integral is 8.Looking back at the options given: A:5, B:6, C:7, D:8. So, the correct answer should be D:8.But wait, just to be thorough, let me visualize the function to make sure I didn't miss any other points where the expression inside the absolute value changes sign.The function is x² - 2x. We found the roots at x=0 and x=2. Since it's a quadratic opening upwards, it will be positive outside the interval [0,2] and negative inside [0,2]. But our limits are from -2 to 2, so indeed, from -2 to 0 it's positive, and from 0 to 2 it's negative. So, the way I split the integral is correct.Alternatively, I can think about the graph of y = x² - 2x. It's a parabola opening upwards with vertex at x = 1, y = (1)^2 - 2*(1) = 1 - 2 = -1. So, the vertex is at (1, -1). So, the graph crosses the x-axis at x=0 and x=2, and between 0 and 2, it's below the x-axis, hence negative. From -2 to 0, it's above the x-axis, hence positive. So, my splitting of the integral is correct.Therefore, I'm confident that the value of the integral is 8, which corresponds to option D.**Final Answer**boxed{D}

question:In the geometric sequence {a_n}, a_3=7, and the sum of the first 3 terms S_3=21, then the common ratio of the sequence {a_n} is ______.

answer:Okay, so I have this problem about a geometric sequence. Let me try to figure it out step by step. The problem says that in the geometric sequence {a_n}, the third term a_3 is 7, and the sum of the first three terms S_3 is 21. I need to find the common ratio of the sequence.First, let me recall what a geometric sequence is. In a geometric sequence, each term after the first is found by multiplying the previous term by a constant called the common ratio, usually denoted by q. So, the nth term of a geometric sequence can be written as a_n = a_1 * q^(n-1), where a_1 is the first term.Given that a_3 = 7, I can write that as:a_3 = a_1 * q^(3-1) = a_1 * q^2 = 7.Also, the sum of the first three terms, S_3, is 21. The sum of the first n terms of a geometric sequence is given by S_n = a_1 * (1 - q^n) / (1 - q) when q ≠ 1. So, for n=3, we have:S_3 = a_1 * (1 - q^3) / (1 - q) = 21.Now I have two equations:1. a_1 * q^2 = 72. a_1 * (1 - q^3) / (1 - q) = 21I need to solve these two equations to find the value of q, the common ratio.Let me see if I can express a_1 from the first equation and substitute it into the second equation. From equation 1:a_1 = 7 / q^2Substituting this into equation 2:(7 / q^2) * (1 - q^3) / (1 - q) = 21Let me simplify this equation step by step. First, multiply both sides by q^2 to eliminate the denominator:7 * (1 - q^3) / (1 - q) = 21 * q^2Divide both sides by 7 to simplify:(1 - q^3) / (1 - q) = 3 * q^2Now, I can factor the numerator on the left side. Remember that 1 - q^3 is a difference of cubes, which factors as (1 - q)(1 + q + q^2). So:(1 - q)(1 + q + q^2) / (1 - q) = 3 * q^2The (1 - q) terms cancel out, assuming q ≠ 1 (since if q=1, the original sum formula would be different, but let's check that later). So we have:1 + q + q^2 = 3 * q^2Let's bring all terms to one side:1 + q + q^2 - 3q^2 = 0Simplify:1 + q - 2q^2 = 0Let me rewrite this equation in standard quadratic form:-2q^2 + q + 1 = 0Multiply both sides by -1 to make it easier:2q^2 - q - 1 = 0Now, I have a quadratic equation in terms of q:2q^2 - q - 1 = 0I can solve this using the quadratic formula. The quadratic formula is q = [ -b ± sqrt(b^2 - 4ac) ] / (2a), where a=2, b=-1, c=-1.Plugging in the values:q = [ -(-1) ± sqrt( (-1)^2 - 4*2*(-1) ) ] / (2*2)Simplify:q = [ 1 ± sqrt(1 + 8) ] / 4q = [ 1 ± sqrt(9) ] / 4q = [ 1 ± 3 ] / 4So, we have two possible solutions:1. q = (1 + 3)/4 = 4/4 = 12. q = (1 - 3)/4 = (-2)/4 = -0.5Wait, so q can be 1 or -0.5. But earlier, I assumed q ≠ 1 when I canceled out the (1 - q) terms. Let me check if q=1 is a valid solution.If q=1, then the geometric sequence would have all terms equal to a_1. So, a_3 = a_1 = 7. Then, the sum of the first three terms would be 3*a_1 = 3*7 = 21, which matches S_3=21. So, q=1 is indeed a valid solution.But let me also check q=-0.5. If q=-0.5, then from equation 1:a_1 = 7 / q^2 = 7 / ( (-0.5)^2 ) = 7 / 0.25 = 28So, a_1=28. Then, the first three terms are:a_1 = 28a_2 = a_1 * q = 28 * (-0.5) = -14a_3 = a_2 * q = -14 * (-0.5) = 7Sum of the first three terms: 28 + (-14) + 7 = 21, which also matches S_3=21. So, q=-0.5 is also a valid solution.Therefore, the common ratio q can be either 1 or -0.5.Wait, but in the problem statement, it's a geometric sequence. If q=1, then all terms are equal, which is a valid geometric sequence, albeit a trivial one. So, both solutions are acceptable.Hence, the common ratio is either 1 or -0.5.**Final Answer**The common ratio of the sequence is boxed{-0.5} or boxed{1}.But since the problem asks for "the common ratio", and both are valid, perhaps we need to present both. However, sometimes in such problems, they might expect the non-trivial solution, which is -0.5. But since both are correct, I think both should be mentioned.Wait, in the initial problem statement, it's just asking for "the common ratio", without specifying whether it's unique or not. So, since there are two possible common ratios, both should be given.But in the original assistant answer, it was written as boxed{-0.5 text{ or } 1}. Maybe that's the way to present it.Alternatively, sometimes in multiple choice or specific answer formats, they might expect both answers boxed separately. But in this case, since it's a fill-in-the-blank, perhaps writing both inside a single box separated by 'or' is acceptable.So, I think the final answer is boxed{-0.5 text{ or } 1}.**Final Answer**The common ratio of the sequence is boxed{-0.5 text{ or } 1}.

Released under the MIT License.

has loaded